1998
DOI: 10.1034/j.1399-3054.1998.1020304.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct responses to copper stress in the halophyte Mesembryanthemum crystallinum

Abstract: Selective gene expression allows the halophyte Mesembryanthemum crystallinum to survive a salt stress. To broaden our understanding of the environmental cues initiating diverse stress responses in this higher plant, unstressed and 0.4 M NaCl‐stressed plants were compared to plants treated with several concentrations of copper (CuSO4), an increasingly relevant environmental heavy metal pollutant. Comparisons of control and copper‐stressed plants included germination, chlorophyll content, accumulation of proline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 0 publications
2
60
1
Order By: Relevance
“…Plant can uptake Cu which is a micronutrient (Thomas et al, 1998). Our study found that Cu concentration in the soil was highest in T5.…”
Section: Heavy Metals Concentration In O Stamineus Plant Partsmentioning
confidence: 51%
“…Plant can uptake Cu which is a micronutrient (Thomas et al, 1998). Our study found that Cu concentration in the soil was highest in T5.…”
Section: Heavy Metals Concentration In O Stamineus Plant Partsmentioning
confidence: 51%
“…The results in Table 1 have shown clearly that, the mean concentration of Cu is higher compared to the published crustal averages. Cu is an important micronutrient for plant (Thomas et al, 1998). It is essential at low concentration but hazardous in plants, animals and human at excessive level.…”
Section: Geochemistry Of the Soil Samplesmentioning
confidence: 99%
“…Heavy metals are taken up into the plant system along with the other nutrients through nutrient absorption process (Liu et al 2007). Cu is considered as an essential micronutrient for plants because of its key role in photosynthesis and other metabolic processes as a cofactor for several enzymes (Thomas et al 1998;Mahmood and Islam 2006;Chatterjee et al 2006). However, presence of excess Cu in growing medium causes phytotoxicity such as leaf chlorosis and retardation in plant growth (MorenoCaselles et al 2000;Lewis et al 2001;Singh and Tewari 2003).…”
Section: Introductionmentioning
confidence: 99%